Mass spectrometry-based proteomic analysis of parathyroid adenomas reveals PTH as a new human hormone-derived amyloid fibril protein. (3rd July 2021) - Colombat, Magali; Barres, Béatrice; Renaud, Claire; Ribes, David; Pericard, Sarah; Camus, Mylène; Anesia, Rodica; van Acker, Nathalie; Chauveau, Dominique; Burlet-Schiltz, Odile; Brousset, Pierre; Valleix, Sophie
Abstract: Background: Congo red-positive material was described in normal and diseased parathyroids (adenoma and hyperplasia) 50 years ago. However, the incidence and the clinical significance of such observation are unknown, and the causal fibril protein has never been convincingly demonstrated. Methods: We conducted the present study including an exceptional case report accompanied with a retrospective study of 105 parathyroid adenomas. We used histopathological, immunohistochemical, ultrastructural, mass spectrometry-based proteomic analysis of parathyroid adenoma tissue samples, and genetic analysis. Results: We describe a 57-year-old man with mild hypercalcemia and elevated parathyroid hormone (PTH) level for whom histopathological analysis revealed a parathyroid adenoma associated with nodular typical amyloid deposits. Tandem mass spectrometry after laser microdissection (LMD-MS) of amyloid adenoma identified PTH as the fibril protein, and no germline mutation in the PTH gene was detected. Congo red-positive PTH-deposits were further observed in 6.6% of the parathyroid adenomas analyzed, and were associated with complete/incomplete or absent universal amyloid signature, but with fibrillar morphology at ultrastructural level. Conclusions: Inappropriate PTH production leads to progressive disease-amyloid aggregation of PTH in a subset of parathyroid adenomas, providing new insights into the pathophysiology of this condition and adding PTH to the list of amyloid protein derived from hormones.